The regulation and function of collagenase-3 (MMP-13) in cutaneous wound healing and squamous cell carcinoma - Toriseva, Mervi (Annales Universitatis Turkuensis D 1010, 2012)
Matrix metalloproteinase-13 (MMP-13) is a potent proteolytic enzyme, whose expression has been previously associated with fetal bone development and postnatal bone remodeling and with adult gingival wound healing. MMP-13 is also known to be involved in the growth and invasion of various cancers including squamous cell carcinoma (SCC) of the skin. The aim of this study was to further elucidate the function and regulation of MMP-13 in wound repair and cancer. In this study, it was shown that fetal skin fibroblasts express MMP-13 in response to transforming growth factor-β in a p38 MAP kinase dependent manner. In addition, MMP-13 was found to be expressed in vivo by wound fibroblasts in human fetal skin grafted on SCID mice. Adenovirally delivered expression of MMP-13 enhanced collagen matrix contraction by fibroblasts in vitro in association with altered cytoskeletal structure, enhanced proliferation and survival. These results indicate that MMP-13 is involved in cell-mediated collagen matrix remodeling and suggest a role for MMP-13 in superior matrix remodeling and scarless healing of fetal skin wounds. Using an MMP-13 deficient mouse strain, it was shown that MMP-13 is essential for the normal development of experimental granulation tissue in mice. MMP-13 was implicated in the regulation of myofibroblast function and angiogenesis and the expression of genes involved in cellular proliferation and movement, immune response, angiogenesis and proteolysis. Finally, epidermal mitogen, keratinocyte growth factor (KGF) was shown to suppress the malignant properties of skin SCC cells by downregulating the expression of several target genes with potential cancer promoting properties, including MMP-13, and by reducing SCC cell invasion. These results provide evidence that MMP-13 potently regulates cell viability, myofibroblast function and angiogenesis associated with wound healing and cancer. In addition, fibroblasts expressing MMP-13 show high collagen reorganization capacity. Moreover, the results suggest that KGF mediates the anti-cancer effects on skin SCC